Utilization of Timed Automata as a Verification Tool for Security Protocols - Koltuksuz, Ahmet; Külahçıoğlu, Burcu; Koltuksuz, Ahmet; Özkan, Murat (Institute of Electrical and Electronics Engineers Inc., 2010)
Timed Automata is an extension to the automata-theoretic approach for the modeling of real time systems that introduces time into the classical automata. It has become an important research area in both the context of formal languages and modeling and verification of real time systems since it was proposed by Alur and Dill in the early nineties. Timed automata proposes an efficient model checking method for verification real time systems having mature and efficient automatic verification tools. One of the application areas of timed automata is the verification of security protocols which are known to be time sensitive. This study aims to make use of timed automata as a verification tool for security protocols and gives a case study on the initial part of the Neuman- Stubblebine Repeated Authentication Protocol. © 2010 IEEE.
4th IEEE International Conference on Secure Software Integration and Reliability Improvement Companion, SSIRI-C 2010; Singapore; Singapore; 9 June 2010 through 11 June 2010
Keywords: Network security; Timed automata; Model checking; Security protocol verification